Edukasi Masyarakat Mengenai Toksikan Abadi (Forever Chemicals) dalam Kosmetik Bersifat Waterproof - Ilmiawati Ilmiawati; Liganda Endo Mahata; Gestina Aliska; Rahmatini Rahmatini; Julizar Julizar; Yusticia Katar; Erlina Rustam; Elly Usman (Warta Pengabdian Andalas, 2023)
Per- and poly-fluoroalkyl substances (PFAS) are synthetic chemicals added to cosmetics for their waterproof property to obtain a long-lasting application. PFAS is highly persistent, hence called the forever chemicals. This community outreach was aimed to educate the public on PFAS exposure through waterproof cosmetics and its health implications. Our webinar was attended by 84 people, 50 of whom responded to the pre-and post-test. An expert delivered the presentation of the educational content. There was an increase in attendees’ test scores from 56.4±21.3 to 88.4±19.0 (mean±SD; paired t-test, p<0.05). The webinar improved attendees’ knowledge of PFAS exposure from waterproof cosmetics and its potential effects on health.